Relationship between Plasma Endocan Level and Clinical Outcome of Chinese Peritoneal Dialysis Patients - Peter Yam-Kau Poon; Jack Kit-Chung Ng; Winston Wing-Shing Fung; Kai-Ming Chow; Bonnie Ching-Ha Kwan; Philip Kam-Tao Li; Cheuk-Chun Szeto (Karger Publishers, 2019)
Background: Endocan is associated with endothelial dysfunction. In peritoneal dialysis (PD) patients, cardiovascular disease is a common cause of mortality. We examined the relationship between serum endocan level and clinical outcome of PD patients. Methods: We recruited 193 new PD patients (118 males, mean age 58.8 ± 11.6 years). Serum endocan levels were determined and stratified into tertile 1 (lowest) to 3 (highest). Nutritional status, arterial pulse wave velocity (PWV) and serum C-reactive protein (CRP) levels were measured. The patients were followed for at least 4 years for clinical outcomes. Results: For the whole cohort, patients with higher serum endocan levels had lower serum albumin and subjective global assessment score, higher carotid-femoral PWV, and higher serum CRP. For patients with suboptimal blood pressure (BP) control, cardiovascular event-free survival was 95.0, 95.5, and 78.5% for tertiles 1, 2, and 3 at 60 months respectively (p = 0.019). Multivariate Cox regression analysis showed that serum endocan level was an independent predictor of cardiovascular event-free survival. No association with cardiovascular event-free survival was found for patients with adequate BP control (95.0, 92.3, and 100% for tertile 1, 2, and 3 at 60 months, respectively, p = 0.6). Conclusions: Higher serum endocan level is associated with unfavourable nutritional, arterial and inflammatory conditions in PD patients. In patients with suboptimal BP control, higher serum endocan is also associated with worse cardiovascular outcome.